Impact of COVID-19 on the education of medical students in Peru: Impacto del COVID-19 en la educación de los estudiantes de medicina del Perú - Pizan Campos, Elizabeth (2020)
The pandemic caused by Severe Acute Respiratory Syndrome 2 (SARS-CoV-2) caused by the Coronavirus disease 2019 (COVID-19) is a highly contagious disease that represents an emergency worldwide. On May 22, 2020 we counted 4,993,470 confirmed cases and 327,738 deaths among 188 countries/regions, at the same time there already existed 111,698 positive cases and 3,244 deaths in Peru already existed; data that will continue to expand and that places thousands of lives in danger, affecting states, municipalities and public and private institutions. In that regard, stricter measures are being taken with the obligatory quarantine, isolation and social distancing management, which directly affects all activities that involve in person gatherings